2022
DOI: 10.1007/s43393-022-00088-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus subtilis Ab03 for efficient ammonia nitrogen removal

Abstract: An efficient ammonia nitrogen degrading bacterial strain was isolated from a fish and shrimp pond and identified as Bacillus subtilis (Ab03). Firstly, the strain was continuously domesticated in ammonium solution to improve its nitrogen removal capacity. The performance of the strain in terms of nitrogen removal efficiency under different culture conditions was then examined. Finally, the nitrogen removal process and related strain mechanisms were analyzed by nitrogen balance. The results showed the strain Ab0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(32 reference statements)
0
1
1
Order By: Relevance
“…Given those advantages with the high growth rate, B. subtilis NCIB3610 seemed to be the most promising host for aquaculture wastewater denitrification. The growth rate we observed for this strain on our AN (ammonium nitrate) medium - 0.34 h − 1 is much higher than the growth rate of the B. subtilis strain Ab03 as observed by Wang et al [ 18 ] and suggested for denitrification of polluted surface water.…”
Section: Discussioncontrasting
confidence: 61%
“…Given those advantages with the high growth rate, B. subtilis NCIB3610 seemed to be the most promising host for aquaculture wastewater denitrification. The growth rate we observed for this strain on our AN (ammonium nitrate) medium - 0.34 h − 1 is much higher than the growth rate of the B. subtilis strain Ab03 as observed by Wang et al [ 18 ] and suggested for denitrification of polluted surface water.…”
Section: Discussioncontrasting
confidence: 61%
“…and Ps. aeruginosa, have been previously reported in marine environments (Zhou et al, 2020;Wang et al, 2022). Bacillus species have been recognized for their significant roles in the nitrogen cycle, including nitrification (Zhao et al, 2020), denitrification (Li et al, 2020), and nitrogen fixation (Yusoff et al, 2011).…”
Section: Discussionmentioning
confidence: 99%